Multiphase flow modeling and optimization design method of dual gas lift for liquid unloading in dual-gas Co-production wells - Cao, Yanfeng; Wu, Guangai; Li, Zhun; Yu, Jifei; Zou, Minghua (Frontiers in Earth Science, 2025)
IntroductionFor reservoirs characterized by vertically superimposed distributions of tight gas and deep coalbed methane (CBM), resource utilization efficiency remains low and economic returns are often poor. Dual-gas co-production offers a promising approach to enhance overall development efficiency. However, significant differences in reservoir pressure, gas–liquid ratio, and fluid properties between the upper and lower reservoirs lead to divergent pressure management strategies. Inappropriate coordination during co-production can result in pressure interference and adversely affect single-well productivity. The dual gas lift technique, with its multi-flow-path capability, is well-suited for accommodating varying reservoir pressures and fluid characteristics, making it particularly advantageous in dual-gas co-production applications.MethodIn this study, the three-flow-path characteristics of the dual gas lift system are considered. A wellbore heat loss model is developed by incorporating heat transfer calculations through the tubing–tubing annulus gas injection channel into the thermal model. Using a “multiphase flow experimental setup with complex internal boundaries,” the flow behavior across different flow paths is analyzed, and a multiphase flow model tailored to dual gas lift operations is established through optimal selection. Based on the properties and development needs of vertically superimposed reservoirs, an optimized design methodology for pressure-divided and zone-specific production in dual gas lift wells is proposed. The full life cycle of a dual-gas co-production well is divided into four stages: initialization and pressure control, stable co-production, decline optimization, and late-stage low production. Corresponding production strategies are formulated for each phase.Result and DiscussionThe results demonstrate that the dual gas lift system can effectively exploit the distinct characteristics of vertically superimposed reservoirs, enabling efficient and coordinated co-production while satisfying drainage and production requirements throughout the well's life cycle. Model predictions were validated against experimental pressure monitoring data, showing a pressure prediction accuracy exceeding 90% across various flow pattern.